2019
DOI: 10.1101/631051
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Host-Microbial Interactions in Systemic Lupus Erythematosus and Periodontitis

Abstract: Systemic lupus erythematosus (SLE) is a potentially fatal complex autoimmune disease, that is characterized by widespread inflammation manifesting tissue damage and comorbidities across the human body including heart, blood vessels, joints, skin, liver, kidneys, and periodontal tissues. The etiology of SLE is partially attributed to a deregulated inflammatory response to microbial dysbiosis and environmental changes. In the mouth, periodontal environment provides an optimal niche to assay local dynamic microbi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The 20 assayed cytokines were: MIP-1α, IL-1β, IL-4, IP-10, IL-6, IL-8, IL-10, IL-12p70, IL-13, IL-17A, IFN-γ, GM-CSF, TNF-α, MIP-1β, IFN-α, MCP-1, P-Selectin, IL-1α, sICAM-1, and E-Selectin. Following manufacturer protocols, all samples were run on a plate with 7 standards (diluted 1:4) and a control (RPMI only), with all samples, standards, and controls run in duplicate (19).…”
Section: Cytokine Analysesmentioning
confidence: 99%
“…The 20 assayed cytokines were: MIP-1α, IL-1β, IL-4, IP-10, IL-6, IL-8, IL-10, IL-12p70, IL-13, IL-17A, IFN-γ, GM-CSF, TNF-α, MIP-1β, IFN-α, MCP-1, P-Selectin, IL-1α, sICAM-1, and E-Selectin. Following manufacturer protocols, all samples were run on a plate with 7 standards (diluted 1:4) and a control (RPMI only), with all samples, standards, and controls run in duplicate (19).…”
Section: Cytokine Analysesmentioning
confidence: 99%
“…Pessoa et al [ 42 ] evaluated the reciprocal impact of periodontal subgingival microbiome on systemic lupus erythematosus and systemic inflammation. Circulating proinflammatory cytokines were upregulated in patients with SLE, inducing an LGI status.…”
Section: Resultsmentioning
confidence: 99%
“…The systemic LGI status seems to be influenced by the composition of the oral microbiome [ 42 ], which changes as a consequence of periodontitis so that higher levels of circulating inflammatory markers have been described in periodontal patients compared to healthy subjects [ 46 , 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the observational studies included in this review presented with a moderate risk of bias 2,3,25–35 , one with high 36 and three with low risk of bias 37–39 (Supplementary , Appendix , Table ). Among the main factors behind study bias we have identified: definition adequacy, representativeness of the cases, selection and definition of the controls, representativeness of exposed cohort and demonstration that outcome of interest was not present at start of study.…”
Section: Resultsmentioning
confidence: 99%